SISTEM MONITORING DAN PENGATUR SUHU OTOMATIS UNTUK KANDANG AYAM DI DESA SUKAMANIS BERBASIS ARDUINO - Pamungkas, Muhammad Teguh; Fergina, Anggun (Jurnal Teknik Informatika UNIKA Santo Thomas, 2021)
One of the problems that occur in nature by chicken breeders is the number of chickens that die, the cause is the room temperature controller in the manual cage as a result the owner forgets to turn on the fan and cooler when the temperature rises, so being in the cage does not match the temperature needed by the chicken. This causes the chicken to become stressed and die. With this research the author aims to make a device that can adjust the room temperature automatically so that the temperature in the cage can be adjusted automatically, so as to reduce the death rate of chickens so that production levels increase. The method used to develop this system is the SDCL method and the microcontroller uses Arduino. The main goal in this study is to make a device that is able to regulate the chicken coop room by means of a fan detecting the temperature is too hot, the temperature can also be monitored using android.